Analisis Akuntabilitas Kinerja Keuangan Satuan Kerja Perangkat Daerah Kota Surakarta - Wahyu Retnaningtyas, Theresia (2016)
The study aims to analyze the influence of budget participation, clarity targets budget, accounting control, system reporting, decentralisation, and superfision fungtional against accountability of the performance of the financial goverments. Based on research result it can be used as material consideration local goverments to improve the performance accountability financial goverment agencies. Testing hypothesis in this research use the analysis regression with test t, test f and the coeficient of the determination (R2). The population in this study is the employees SKPD city of Surakarta. A sample of the methods use is multistage sampling. Based on the criteria has outlined above, then obtained 23 SKPD as a sample. Based on the result of research is known that : 1)Participation budget not influential on accountability of the performance financial employee of SKPD city of Surakarta, so H1 rejected. 2) Clarity targets budget influential significant against accountability SKPD financial performance of the city Surakarta, so H2accepted. 3) The accounting control not influential on accountability SKPD financial performance of the city Surakarta, so H3rejected. 4) The system reporting influential significant against accountability SKPD financial performance of the city Surakarta, so H4accepted. 5) decentralisation influential significant against accountability of the performance of the financial employees SKPD Surakarta city, so H5accepted. 6) Supervision fungtional influential significant against accountability of the performance of the financial employees SKPD Surakarta city, so H6accepted